Vitamin C Intake and Ischemic Stroke - Xiaolong Tang; Hanguang Liu; Yuan Xiao; Lei Wu; Peng Shu (Frontiers in Nutrition, 2022)
Vitamin C is an essential micronutrient with important antioxidant properties. Ischemic stroke is a major public health problem worldwide. Extensive evidence demonstrates that vitamin C has protective effects against cardiovascular disease, and there is a close relationship between vitamin C intake and ischemic stroke risk. Based on the evidence, we conducted this umbrella review to clarify the relationship between vitamin C intake and ischemic stroke risk from four perspectives: cellular mechanisms, animal experiments, clinical trials, and cohort studies.